Dural Septation on the Inner Surface of the Jugular Foramen: An Anatomical Study - Tubbs, R. Shane; Griessenauer, Christoph J.; Bilal, Muhammad; Raborn, Joel; Loukas, Marios; Cohen-Gadol, Aaron A. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Introduction Preserving cranial nerve (CN) function during tumor removal at the jugular foramen is challenging. No anatomical study has better defined the relevant dural septations on the inner surface of the jugular foramen. This study was undertaken to elucidate this anatomy.Methods Fourteen cadaveric heads (28 sides) were dissected, and relationships of the meningeal coverings of the jugular foramen and adjacent CNs documented. A classification scheme was created to better describe the dural septations of the inner surface of the jugular foramen.Results Four types of dural septations were noted. Type I: 10 sides (36%) where a dural septation was seen between CNs IX anteriorly and X and XI posteriorly. Of these, the septum was ossified in 20%. Type II (32%) was defined as a jugular foramen with no dural septation. Type III (7%) was defined as septation between CNs IX and X anteriorly and XI posteriorly. Type IV (7 sides, 25%) or the chaotic form was defined as multiple septations within the jugular foramen that housed and divided CN rootlets.Conclusions The dural septations defined here can be used in future studies to help correlate operative strategy to meningeal morphology within the jugular foramen.
Keywords: skull base; posterior fossa; cranial anatomy; meninges; jugular foramen; anatomy